Real‐world on‐treatment and initial treatment absolute risk differences for dabigatran vs warfarin in older US adults. Issue 8 (15th July 2020) - Webster‐Clark, Michael; Stürmer, Til; Edwards, Jessie K.; Poole, Charles; Simpson, Ross J.; Lund, Jennifer L.
Abstract: Purpose: Trials and past observational work compared dabigatran and warfarin in patients with atrial fibrillation, but few reported estimates of absolute harm and benefit under real‐world adherence patterns, particularly in older adults that may have differing benefit‐harm profiles. We aimed to estimate risk differences for ischemic stroke, death, and gastrointestinal bleeding after initiating dabigatran and warfarin in older adults (a) when patients adhere to treatment and (b) under real‐world adherence patterns. Methods: In a 20% sample of nationwide Medicare claims from 2010 to 2015, we identified beneficiaries aged 66 years and older initiating warfarin and dabigatran. We followed individuals from initiation until death or October 2015 (initial treatment, IT) and separately censored individuals' follow‐up after drug switches and gaps in supply (on‐treatment, OT). We applied inverse probability of treatment and standardized morbidity ratio weights, as well as inverse probability of censoring weights, to estimate two‐year risk differences (RDs) for dabigatran vs warfarin. Results: We identified 10, 717 dabigatran and 74, 891 warfarin initiators. Weighted OT RDs suggested decreased ischemic stroke risk for dabigatran vs warfarin; IT RDs indicated increased or no change in ischemic stroke risk. Regardless of follow‐up approach and weighting strategy, risk of death appeared lower and risk of gastrointestinal bleeding appeared higher when comparing dabigatran vs warfarin. Conclusions: Dabigatran use was associated with lower risks of mortality and ischemic stroke in routine care when older adults stayed on treatment. IT analyses suggested that these benefits may be diminished under real‐world patterns of switching and discontinuation.